EVALUASI PASCA HUNI BANGUNAN SDN 01 SENTONO - Jamalul Lail (UII, 2015)
SDN 01 Sentono is one of the elementary schools for people in Sentono Village. Post Occupancy Evaluation (POE) is important to do to know about the performanceof the buildings and also to determine the effectiveness and efficiency of theperformance of the building in the shade of the school function.